2015
DOI: 10.1016/j.neuro.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Low-level repeated exposure to diazinon and chlorpyrifos decrease anxiety-like behaviour in adult male rats as assessed by marble burying behaviour

Abstract: Occupational exposure to organophosphate (OPs) pesticides is reported to increase in the risk of developing anxiety and depression. Preclinical studies using OP levels, which inhibit acetylcholinesterase activity, support the clinical observations, but little is known of the effects of exposure below this threshold. We examined the effects of low level OP exposure on behaviours and neurochemistry associated with affective disorders. Adult rats were administered either diazinon (1 mg/kg i.p.) which is present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 54 publications
4
23
1
Order By: Relevance
“…We have previously reported that marble burying behaviour is a sensitive behavioural measure of low level OP exposure (Savy et al, 2015), and the current study supports this. Marble burying behaviour is frequently described as an ethological measure of anxiety in rodents and has been used to screen anxiolytic drugs in rodents (Broekkamp et al, 1986;Njung'e and Handley, 1991).…”
Section: Behavioursupporting
confidence: 88%
See 3 more Smart Citations
“…We have previously reported that marble burying behaviour is a sensitive behavioural measure of low level OP exposure (Savy et al, 2015), and the current study supports this. Marble burying behaviour is frequently described as an ethological measure of anxiety in rodents and has been used to screen anxiolytic drugs in rodents (Broekkamp et al, 1986;Njung'e and Handley, 1991).…”
Section: Behavioursupporting
confidence: 88%
“…In addition, we assessed AChE and butrylcholinesterase (BChE) activity in blood and brain to determine if OP exposure was below the threshold to inhibit ChE activity, and also marble-burying behaviour during the chronic exposure period. Marble burying behaviour is an ethological measure of anxiety in rodents, and we have found that it is a sensitive behavioural measure of low level OP exposure (Savy et al, 2015).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Animal studies have demonstrated that OP pesticide exposure levels even below the threshold for acetylcholinesterase inhibition can alter psychological disorder related gene expression (Savy et al, 2018), induce changes in behavior and neurochemistry (Savy et al, 2015), and result in cognitive impairments (dos Santos et al, 2016; Terry, 2012). Moreover, low level OP pesticide exposure can change neuronal cell development (Slotkin et al, 2008), induce oxidative stress (Slotkin and Seidler, 2010; Zafiropoulos et al, 2014), and influence the thyroid hormone levels and the reproductive system (Androutsopoulos et al, 2013; De Angelis et al, 2009; Haviland et al, 2010).…”
Section: Introductionmentioning
confidence: 99%